MANAGEMENT OF LEADERSHIP EDUCATION OF SANTRI IN PONDOK PESANTREN - Badrud Tamam; Ahmad Farihin (Universitas Ahmad Dahlan, 2020)
This research studies about leadership education in pondok pesantren by focusing on aspects of planning, organizing, actuating, and controlling in the management of leadership education santri. The aims are to obtain a comprehensive description of the implementation of the management functions which include planning, organizing, actuating, and controlling in leadership education santri at pondok pesantren. Qualitative approach used in this study. Interview, observation and documentation used as a data collection tools. interactive model of data analysis was employed to analyze the data in this study with consist of three activities which are data reduction, data display, and conclusion. The reliability of results were obtained with four criteria are: credibility, transferability, dependability, and confirmability. The results showed planning implementation include the formulation of the program, the establishment of the curriculum, and grouping santri based on the level of maturity of leadership. Organizing involves the division of tasks and the establishment of working groups. Actuating includes training and coaching santri in conducting leadership training program. Controlling includes reporting and evaluation. Recommendations from the study's findings are all the components should always complement and maintain continuity of leadership education program santri. In addition, organize activities that support the achievement of leadership education programs.